2015
DOI: 10.1038/bmt.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Impact of length of cryopreservation and origin of cord blood units on hematologic recovery following cord blood transplantation

Abstract: As the history of the cord blood banking system has lengthened, the number of cord blood units (CBUs) cryopreserved for years has increased. The global expansion of cord blood banking resulted in active international exchange of CBUs. To determine whether long-term cryopreservation and international shipment of CBUs affect the quality of the units and outcome after transplantation, we retrospectively analyzed the quality of 95 CBUs and the hematologic recovery of 127 patients with hematological malignancy foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Marrow is usually cryopreserved in 10% DMSO, and studies have shown that marrow, as well as peripheral blood stem cells and umbilical cord blood, may remain cryopreserved for a long period of time (>10 years) while retaining stem cell/progenitor activities for use in clinical practice. [12][13][14] Shen and colleagues demonstrated that marrow preserved for 23 to 25 years was effective for MSC culture production with adequate growth characteristics and adequate amounts of adherent, healthy MSCs. 15 Those authors investigated old frozen marrow specimens as starting material (n 5 20) for MSCs, but the controls (n 5 20) were not paired from the same donors.…”
Section: Discussionmentioning
confidence: 99%
“…Marrow is usually cryopreserved in 10% DMSO, and studies have shown that marrow, as well as peripheral blood stem cells and umbilical cord blood, may remain cryopreserved for a long period of time (>10 years) while retaining stem cell/progenitor activities for use in clinical practice. [12][13][14] Shen and colleagues demonstrated that marrow preserved for 23 to 25 years was effective for MSC culture production with adequate growth characteristics and adequate amounts of adherent, healthy MSCs. 15 Those authors investigated old frozen marrow specimens as starting material (n 5 20) for MSCs, but the controls (n 5 20) were not paired from the same donors.…”
Section: Discussionmentioning
confidence: 99%
“…The capability of CD34þ cells to be stored for more than 10 years is proven in cord blood units and reviewed extensively [24][25][26][27] , but these results are not directly comparable with PBSC, where the CD34þ cells are being mobilized from their natural environment and cryopreserved accompanied with highly activated neutrophils. Our study showed that the viability of leukocytes declined with long-term storage (68% after 10 years); however, the viability of mononuclear and CD34þ cells was retained with <10% decrease in comparison to native products.…”
Section: Discussionmentioning
confidence: 99%
“…Umbilical cord blood (UCB) is a particularly promising source of stem and progenitor cells that is appealing for treatment of perinatal brain injury-UCB is readily available at birth for routine collection, particularly in situations of compromised (preterm or term asphyxia) births; contains large numbers of mononuclear cells with a heterogeneous population of stem and progenitor cells [76]; has low immunogenicity and low risk of rejection, therefore allowing the potential for allogeneic administration [77]. UCB cells demonstrate high plasticity with an eightfold greater proliferation potential compared to other cell sources such as bone marrow [78]; and can be stored for long periods of time, with studies showing that, after 10+ years of cryopreservation, viable cell recovery is still very high [79].…”
Section: Umbilical Cord Blood As a Therapy For Perinatal Brain Injurymentioning
confidence: 99%